The implications of the PNAE on the practices of family farmers and the generation of opportunities for development - Bastos, Rosária Cal; Loreto, Maria das Dores Saraiva de; Emmendoerfer , Magnus Luiz; Souza, Gustavo Bruno Pereira de (Seven Editora, 2024)
This article aimed to identify the limits, the possibilities of action and empowerment of social actors in the implementation of the program, focusing on personal and social development, considering the operationalization of the PNAE, in the light of the Theories of Social Networks, Theory of Social Practice and Development. A quantitative-qualitative approach was used as a methodological procedure, based on the case study, involving 07 municipalities in the Zona da Mata of Minas Gerais, through 53 semi-structured interviews applied to family farmers, whose data were analyzed through the triangulation of manual and automated techniques by the IRaMuTeQ software and Microsoft Office Excel. The results identified that the profile of family farmers meets the characteristics that the PNAE seeks to promote, and pointed out the contributions and challenges involved in the process of implementing the program. It also shows that the interaction of family farmers in the PNAE’s social networks can influence their actions and perceptions, shaping their behaviors according to the structure in which they are inserted. It is concluded that the PNAE plays a significant role in personal and social development, but that there are challenges, such as excessive bureaucracy, delay in public calls, lack of interest of family farmers in participating in the PNAE, barriers to the creation of cooperatives and associations, among others, which need to be rethought and overcome to further advance the development of the region. DOI:https://doi.org/10.56238/sevened2024.007-024